Complications of Percutaneous Irreversible Electroporation for Pancreatic Cancer: A Systematic Review - Harsimran Bhatia; Muniraju Maralakunte; Mudita Gulati; Vishal Sharma; Pankaj Gupta (Journal of Clinical Interventional Radiology ISVIR)
Objective The aim of the study was to systematically review the percutaneous irreversible electroporation (IRE) complications for pancreatic ductal adenocarcinoma (PDAC).